Farming, resistance and coping in the occupied West Bank - Wendler, Mascha (2018)
Farming has a long cultural tradition in the occupied Palestinian territories (oPt) but today it is affected by the Israeli occupation. This thesis investigates how different agricultural actors in the West Bank frame farming as a practice and what collective action frames they have developed connected to their understanding of farming. The aim is to illuminate how these different actors construct meaning around the practice of farming, and how people can understand and use farming in different ways. Some of my informants clearly link farming practices to a bigger symbolism of farming as a practice of resistance against the Israeli occupation of Palestinian territories. Little attention has been given to the non-violent resistance in the occupied Palestinian territories and esspecially to farming as a tool of resistance. However, not all of my informants align the same symbolism to the practice of farming, as for some of the informants it is considered to be foremost a coping strategy.